Apoptosis pada Penyakit Neurodegeneratif - Chyntia M. Sahetapi; June M. M. Luhulima; Abraham Simatupang; Marwito Wiyanto; Jan S. Purba (Majalah Kedokteran UKI, 2014)
Abstrak Apoptosis atau kematian sel yang terencana adalah komponen normal perkembangan dan kesehatan organisme multiselular. Kematian sel merupakan respons dari berbagai rangsangan, yang selama proses apoptosis hal itu berjalan secara terkendali. Faktor genetik dan lingkungan yang bertanggung jawab terhadap penyakit neurodegeneratif, telah terbukti memiliki jalur yang sama dengan apoptosis, melibatkan stres oksidatif, homeostasis kalsium yang terganggu, disfungsi mitokondria, dan aktivasi protease sistein yang disebut kaspases. Kaskade kematian tersebut dapat dicegah oleh sinyal sintas, yang menekan radikal bebas dan menstabilkan homeostasis kalsium dan fungsi mitokondria. Sel di dalam sistem saraf pusat ikut mati pada penyakit neurodegeneratif akut maupun kronis. Hal itu mendasari gejala gangguan neurologis pada manusia, termasuk Alzheimer, Parkinson dan penyakit Huntington, stroke dan amyotrophic lateral sclerosis.Kata kunci: apoptosis, homeostasis, mitokondria, penyakit neurodegeneratif Abstract Apoptosis or programmed cell death is a normal component of the development and health of multicellular organisms. Cells die in response to a variety of stimuli and during apoptosis they do so in a controlled, regulated fashion. The identification of specific genetic and environmental factors responsible for these diseases has bolstered evidence for a shared pathway of apoptosis, involving oxidative stress, perturbed calcium homeostasis, mitochondrial dysfunction, and activation of cysteine proteases called caspases. These death cascades are counteracted by survival signals, which suppress oxyradicals and stabilize calcium homeostasis and mitochondrial function. By the identification of mechanisms that either promote or prevent neuronal apoptosis come new approaches for preventing and treating neurodegenerative disorders. Cells within the central nervous system die during both acute and chronic neurodegenerative disorders and underlie the symptoms of many human neurological disorders, including Alzheimer’s, Parkinson’s and Huntington’s diseases, stroke, and amyotrophic lateral sclerosis.Key words: apoptosis, homeostasis, mitochondria, neurodegenerative disorder